2002
DOI: 10.1081/jdi-120004093
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Intravenous Calcitriol in Secondary Hyperparathyroidism: The Role of Technetium-99m-Mibi Scintigraphy in Predicting the Response to Treatment

Abstract: We conclude that MIBI scan is a reliable technique in predicting the response to treatment with i.v. calcitriol in patients with secondary hyperparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As a result of pathological changes that occur during parathyroid gland hyperplasia, the utility of current SHPT treatment modalities can be compromised. In severe or refractory SHPT, when parathyroid glands are grossly enlarged or exhibit monoclonal growth patterns, patients can become resistant to vitamin D therapy (24,89,107). This may be the result of a significant reduction in the expression of VDRs that negates the actions of vitamin D sterols.…”
Section: The Car and Management Of Shptmentioning
confidence: 99%
“…As a result of pathological changes that occur during parathyroid gland hyperplasia, the utility of current SHPT treatment modalities can be compromised. In severe or refractory SHPT, when parathyroid glands are grossly enlarged or exhibit monoclonal growth patterns, patients can become resistant to vitamin D therapy (24,89,107). This may be the result of a significant reduction in the expression of VDRs that negates the actions of vitamin D sterols.…”
Section: The Car and Management Of Shptmentioning
confidence: 99%
“…It was shown that MIBI-scan could be used to evaluate parathyroid function as well as response to treatment with calcitriol [22, 23]. In our case with positive basal MIBI-scan after the inhibition test with calcitriol (2  μ g i.v.…”
Section: Discussionmentioning
confidence: 79%
“…Imaging of the parathyroid glands has been used in the identification of solitary parathyroid adenomas, which is the most common finding in patients with primary HPT [1]. parathyroid scintigraphy [3][4][5][6][7][8][9][10][11][12][13][14][15][16] and ultrasound (US) [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], have been assayed to establish their possible utility in SHP. Recently, preoperative non-invasive imaging tools, i.e.…”
Section: Introductionmentioning
confidence: 99%